Uma universidade em fund(ação): as contribuições da psicanálise para a análise do discurso institucional da UNILA - Gastaldin, Carla da Conceição Mores (2018)
The objects of study of this research are the discourse of the Administrative Technicians in Education (TAE's that entered the first contest of the university) and the official institutional discourse on the project of Latin American integration, in the context of UNILA. Research conceived the institution as a human creation, founded by a discourse and a desire that sustains it, which serve as a foundation for its existence. Already the discourse was understood as a chain of signifiers articulated and provisionally linked together, a configuration that can be constantly altered through the significant slip process. The objective of this work was to compare the official discourse of the university with the discourse of the APS, so that the concordances and contradictions between the discourses could be identified. The methodology used to treat the data was the discourse analysis under the psychoanalysis approach, from which it was possible to identify important signifiers in the history of the institution, which appeared interconnected to the theme of integration. The observance of the repetition of signifiers directed the work of analysis, through which it was possible to recognize several contradictions between the discourses analyzed, besides pointing out what is configured as an institutional symptom. The main symptoms evidenced from the discourse analysis were: the lack of planning, the delay in internal processes and institutional development, the lack of recognition of diplomas (issued by UNILA) abroad, evasion, difficulty in carrying out the works of the university campus and the difficulties of interpersonal relationship, as well as with society and with partner institutions. It was concluded that the difficulties encountered by the university reflect the obstacles historically faced in the realization of the ideal of Latin American integration, as well as the political dimensions of institutional history and the difficulties inherent in everything that has a human dimension and, therefore, a lack of it.